A case of unusual root morphology: Maxillary canine with two roots - Nagesh Bolla; Sarath Raj Kavuri (Wolters Kluwer Medknow Publications, 2009)
The case describes a 3 months follow-up of the treatment of a maxillary canine with two roots. Clinical examination revealed a maxillary canine with a large carious lesion and an exaggerated response to cold thermal tests. Radiographic examination revealed a large distal carious lesion that appeared to invade the pulp chamber. The radiograph also revealed what appeared to be an extra root in this permanent maxillary canine.